Investigation of the process of surfacing and vibration deformation during the restoration of plowshares and discs of tillage machines - Marchenko, D.D.; Matvyeyeva, K.S. (Problems of Tribology, 2021)
The analysis of ploughshare wear is given in the article and the characteristic requirements to the technological process of restoration of their worn surfaces are established. The choice of restoration technology was justified taking into account the nature of defects and the degree of wear of the working surfaces of cutting elements, their material, hardness, design parameters, accuracy of processing and cost of repairs. Quantitative and qualitative assessment of the reliability of the cutting elements of the plowshares of tillage machines, restored by different methods, was carried out by comparison with the same indicators of the new ones. Analysis of the condition of restored and new plowshares was carried out on their wear in the process of laboratory and operational tests. Laboratory researches on strengthening of plowshares by a method of vibration deformation were carried out on the specially made installation consisting of the following main knots: vibroexciter IV-105 with adjustable unbalance; hydraulic lifting systems; auxiliary equipment. The deformation rate was regulated by a V-belt double-circuit variator of the pump drive. To study the effect of normal and vibration load on the strength characteristics of the processed material, the study was performed on samples-models, and then - on the details. The samples were new plowshares, experimental studies on which provided the identity of the nature of the course of wear of their cutting elements. It is experimentally established that the hardness of the material on the surface of the blade, depending on the technological process of restoration was: restored by welding tires of steel 45 with surmaite surfacing and vibration hardening - 71-74 HRC; new plowshares made of L-53 steel, subjected to vibration hardening 66-68 HRC; new from 65G steel and strengthened by vibration deformation 57-59 HRC.